Epizootic ulcerative syndrome (EUS) in bata, Labeo bata (Hamilton 1822) from Tripura, India - Baruah, Arunjyoti; Kamilya, Dibyendu; Saha, Ratan Kumar (Indian Journal of Fisheries, 2014)
The occurrence of epizootic ulcerative syndrome (EUS) in bata (Labeo bata) and the infectivity and role of Aphanomyces invadans in the aetiology of ulcerative condition were investigated in the present study. Live fish (L.bata) samples with ulcerations were collected from a local fish farm in Tripura and were acclimatised in laboratory tanks with proper management. Case histories, clinical and gross signs of the sampled fishes were recorded. Histopathological study of muscle and liver tissue from the ulcerated fish showed the presence of oomycete hyphae and granulomas. Oomycete isolation was done from the affected muscles and was identified as Aphanomyces invadans based on colony morphology, growth and microscopic morphology. The results suggest that the ulcerative condition in bata was due to EUS associated with A. invadans.